1989
DOI: 10.1002/j.1551-8833.1989.tb03245.x
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Study of the Leaching of Lead From Water Faucets

Abstract: Twelve faucets, representing various designs, materials of construction, and manufacturers, were studied in the laboratory to develop additional information about the leaching of lead and other metals from common kitchen faucets. It was found that new cast‐brass faucets could contribute lead to drinking water in excess of the proposed no action level of 10 μg/L. Also, 60–75 percent of the lead leached from a faucet appeared in the first 125 mL of water collected from the faucet. After 200–250 mL of water had f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…In 1988, the Environmental Protection Agency (EPA) proposed a new regulation for controlling the concentration of lead and copper in drinking water. 6 The proposed action limits were 0.005 mg/L for lead and 1.3 mg/L for copper, as measured at the tap. These have recently been changed 17 to 0.015 mg/L for lead and 1.3 mg/L for copper.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…In 1988, the Environmental Protection Agency (EPA) proposed a new regulation for controlling the concentration of lead and copper in drinking water. 6 The proposed action limits were 0.005 mg/L for lead and 1.3 mg/L for copper, as measured at the tap. These have recently been changed 17 to 0.015 mg/L for lead and 1.3 mg/L for copper.…”
Section: Introductionmentioning
confidence: 90%
“…Most studies [5][6][7][8][9][10][11] have reported no enhanced leaching of metals such as Pb, Cu, Zn, Cr, and Cd from water distribution system components. These have involved studies of the leaching of lead from brass water faucets, 5,6 from lead solder, 7,8 from lead pipe, 7,9 and from brass fittings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amounts of metal leached from various components of the water distribution system are usually highest in the first flush samples and thereafter decrease with the volume of water flushed through the faucet [5,[35][36][37]. Thus, by the time 200-250 ml.…”
Section: Impact Of Faucets and Fittingsmentioning
confidence: 99%